Intracranial atherosclerosis: structure, clinical aspects and risk factors - Marine M. Tanashyan; Andrey S. Mazur; Anton A. Raskurazhev; Anna N. Berliand; Marina V. Dreval; Polina I. Kuznetsova; Оlga V. Lagoda (Анналы клинической и экспериментальной неврологии)
Introduction. Atherosclerosis is a complex pathophysiological process with a wide range of clinical manifestations. Active research is underway to determine the prevalence of intracranial atherosclerosis across different ethnic groups, the role of modifiable and non-modifiable risk factors in its pathogenesis, and the advances in diagnostic algorithms for patients with extra-/intracranial atherosclerosis.